Relationship Between Knowledge And Work With Medication Adherence Among Pulmonary Tuberculosis Patients At The Dempo Health Center In Palembang City - Dwi Salsabilah; Henni Febriawati; Riana Dewi; Sri Aisyah Hidayati (Catholic University Musi Charitas, 2024)
WHO noted that in 2022 the number of people diagnosed with TB globally will be 7.5 million. Indonesia is the second country with the highest number of TB sufferers, amounting to 658,543 cases according to data from the Indonesian Ministry of Health, one of the provinces with the highest number of TB cases in South Sumatra. Tuberculosis is an infectious disease caused by bacteria in the form of bacilli or rods called mycobacterium tuberculosis. Compliance with taking medication occurs for the success of taking medication in pulmonary TB sufferers. This study aims to determine the relationship between knowledge and work and compliance with taking medication for pulmonary TB sufferers at the Dempo Community Health Center, Palembang City in 2024. The research was conducted on 20 May – 20 June 2024, this research used a cross sectional research design. The total sample was 41 people. The sampling technique is accidental sampling. The results show that there is a relationship between knowledge and adherence to taking medication in pulmonary TB sufferers (p = 0.005) with an OR value = 9.333, and there is a relationship between work and adherence to taking medication in pulmonary TB sufferers (p = 0.033) with an OR value = 20.693. Based on research results, the availability of many drugs is influenced by several knowledge factors to increase awareness, and work factors related to stress that a person can experience. Dempo Community Health Center is expected to always provide education to patients and patient families regarding the importance of compliance in TB treatment and the risks that will occur if they do not comply.